Identification and characterization of novel elastin gene mutations in eleven families with supravalvular aortic stenosis - Zhou, Jianrong; Wu, Yueheng; Xu, Xiaoli; Zhang, Yong; Zhang, Xiong; Chen, Haisheng; Zhuang, Jian; Chen, Jimei; Teng, Yun (Frontiers in Genetics, 2022)
Background: Supravalvular aortic stenosis (SVAS) is a rare congenital heart disease affecting approximately 1 in 25,000 live births. In some patients it is accompanied by pulmonary artery stenosis, particularly of pulmonary artery branches. Chronic stenosis can lead to cardiac hypertrophy and even circulatory failure. Familial autosomal dominant SVAS is frequently associated with elastin (ELN) gene mutations, whereas Williams-Beuren syndrome is a complex developmental disorder caused by heterozygous microdeletions of 26 – 28 genes at 7q11.23, including ELN. Methods: Whole-exome sequencing was performed in 42 individuals from 11 Chinese families with SVAS to identify the pathogenic gene mutations involved. Aortic tissue was obtained for histological analyses, and quantitative reverse-transcription-PCR and western blotting were used to verify the expression of elastin molecules. Results: Five point mutations and six frameshift mutations in the ELN gene were detected in the peripheral blood of all investigated families. Nine were nonsense mutations that result in premature stop codons, and the other two were missense mutations. All variants were heterozygous. Nine of the variants were novel, and have not been included in databases or previously reported. One mutation occurred in individuals from two different families. Reduced elastin protein expression was evident in patients’ aortic tissue. Conclusions: The novel mutations of ELN were found to be pathogenic, which confirmed by reduced elastin expression and leads to SVAS. Thus, detailed cardiac testing and genetic counseling are warranted for patients and asymptomatic individuals with these mutations.